Access and Privatization of Higher Education in Central Asia - Shaldarbekova, Amina (International Higher Education, 2024)
Higher education enrollment rates in Central Asia are closely related to the level of privatization. The higher the degree of privatization, the higher the access to higher education. Although public higher education has been partially privatized in the region’s four countries, Kazakhstan and Kyrgyzstan have also facilitated access to higher education by permitting private universities, while Uzbekistan and Tajikistan have maintained strict state regulation. The number of tuition-paying students vs. state-funded students is growing, too.